Essays on small open economy macroeconomics - Hanna Freystätter (Bank of Finland, 2012)
Chapter 1: Introduction 9 Chapter 2: Price setting behaviour in an open economy and the determination of Finnish foreign trade prices 29 Chapter 3: Financial market disturbances as sources of business cycle fluctuations in Finland 79 Chapter 4: Financial factors in the boom-bust episode in Finland in the late 1980s and early 1990s 127
URN:NBN:fi:bof-201408071692
Keywords: 330; Kleine offene Volkswirtschaft; Dynamisches Gleichgewicht; Außenhandelspreis; Finanzmarkt; Schock; Akzelerator; Konjunktur; Finnland